Sowing the wheat seeds of Afghanistan's future - Poole, Nigel D.; Sharma, Rajiv Kumar; Nemat, Orzala A.; Trenchard, Richard; Scanlon, Andrew; Davy, Charles; Ataei, Najibeh; Donovan, Jason A.; Bentley, Alison R. (Wiley, 2022)
Afghanistan is a country with diverse natural ecologies in a largely arid and mountainous region. The rural sector is still considered to drive economic potential. Current social, political and economic instability along with climatic challenges are driving food and water insecurity in the wider region. In the short term, it is likely that this and the associated challenges of displacement and unemployment can only be addressed by humanitarian intervention and agrifood and nutrition support. In the medium to long term, drought, and heat, probably linked to climate change, will pose recurrent challenges for agriculture and food security that will require a much broader set of interventions to secure the rural population's livelihoods. The genetic gap, among other major challenges, must be addressed if Afghanistan is to develop its agricultural potential leading to income and livelihood improvements for farmers and stable and accessible supplies for consumers. Only thereby will the country be enabled to reap the important and long-sought trade and food security benefits derived from self-sufficiency. Here, we highlight the agricultural challenges facing Afghanistan and propose forward strategies for ensuring the future stability of wheat production, the cornerstone of Afghan agriculture.